Coagulation-flocculation of combined chemical mechanical polishing wastewater and flouride-containing wastewater from a semiconductor manufacturer - De Luna, Mark Daniel G. (2007)
The semiconductor industry is crucial to the technological advancement of modern society. Its rapid growth has brough about increasing demands of ultra pure water especially for chemical mechanical polishing (CMP) and fluoride containing wet-etching unit operations. the study aims to determine the effects of a combined treatment of CMP wastewater and fluoride-containing wastewater from a semiconductor manufacturer using conventional coagulation-flocculation process with CaCI2.2H2O as coagulant. Synthetic wastewater contained 640 ppm F was prepared from reagent grade NaF (99.5%, Acros) and actual CMP wastewater from a semiconductor manufacturer at Hsin-Chu Science Park, Taiwan. Given Taiwan's maximum tolerable industrial effluent discharge concentration of 15 ppm F, at coagulant dosage of [Ca2+/F] = 0.5 and pH =7.00 +- 0.02, CMP/F volume ratios of 0:1, 1:1, 2:1 and 4:1 resulted in residual fluoride concentrations 18.10 ppm, 10.8 ppm, 1045 ppm and 12.60 ppm alongside decreasing zeta potential measurements respectively. Under the same conditions but at [Ca2+/F] = 0.75, the CMP/F volume ratios corresponded to residual fluoride concentrations of 8.69 ppm, 4.52 ppm, 3.35 ppm and 3.60 ppm respectively following a similar zeta potential trend. Conductivity values for the suspensions with [Ca2+/F] = 0.5 and [Ca2+/F] = 0.75 were 3.5 mS and 4.5 mS respectively. Various flocculants were compared and anionic polymer, PPA (molecular weights 90, 000 g/mol and 450, 000 g/mol) were found to be effective in bringing residual turbidity values down to 1 NTU at low flocculant dosage.